Effects of Ivy (Hedera helix) Leaf Extract on Growth, Digestive Enzyme Activity, Hematological Parameters, Innate Immunity, and the Expression of Immune-Related Genes in Rainbow Trout (Oncorhynchus mykiss) - Raha Fadaei; Ahmad Noori; Arash Akbarzadeh; Seyed Hossein Hoseinifar; Marina Paolucci (Aquaculture Nutrition, 2025)
Herbal bioactive compounds are effective in enhancing the antioxidant and immune status of fish, as they effectively neutralize oxidative stress. The present study examined the effectiveness of Ivy (Hedera helix) leaf extract (ILE) on growth performance, immune responses, antioxidant parameters, and the expression of immune-related genes in rainbow trout (Oncorhynchus mykiss). Four test diets were prepared as follows: a control diet at 0 mg of ILE (ILE0) and diets of 100 mg (ILE100), 150 mg (ILE150), and 200 mg (ILE200) of ILE/kg. A total number of 240 rainbow trout, with an initial weight of 6.38 ± 0.30 g, were divided into 12 tanks and fed on the experimental diets for 8 weeks. Results indicated that ILE150 and ILE200 exhibited significantly higher final weight (FW), weight gain, and specific growth rate compared to the control and ILE100 treatments. Additionally, fish fed with ILE showed significantly higher activity of digestive enzymes, including trypsin, pepsin, proteases, lipase, and amylase compared to the control group. The experimental diets also significantly affected hematological indices, including erythrocytes, leukocytes, hematocrit, hemoglobin, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration, and mean corpuscular hemoglobin, and their highest levels were observed in ILE150 and ILE200. Furthermore, a notable reduction was observed in aspartate aminotransferase (AST), alanine transaminase (ALT), and alkaline phosphatase (ALP) activities in all ILE-supplemented diets. Serum antioxidant enzymes, including catalase (CAT), glutathione peroxidase (GPX), and superoxide dismutase (SOD), significantly increased in ILE150 and ILE200, but serum malondialdehyde (MDA) levels significantly declined in treatments fed with ILE compared to the control group. Alternative complement, total immunoglobulin, total protein, and lysozyme levels were significantly higher in ILE-supplemented-diet treatments. The results also showed a significant upregulation of immune-related genes, such as interleukin 1β, interleukin-6, interleukin-8, and lysozyme, in ILE150 and ILE200 compared to the control and ILE100. In conclusion, administering ILE at doses of 150–200 mg/kg diet could improve the growth performance and immune-antioxidant capacity of rainbow trout.